2000
DOI: 10.1021/ie000554a
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Modeling of Combined Ion-Exchange and Molecular Adsorption Phenomena

Abstract: A thermodynamic framework is presented for modeling combined ion-exchange and molecular adsorption phenomena at a solid−liquid interface. The analysis of the uptake of both ionic and molecular species by the solid surface is based on the concept of exchange reactions. The adsorption model is coupled with a previously developed comprehensive thermodynamic speciation model for the aqueous phase. A parameter regression procedure is developed that decouples the determination of equilibrium constants from the evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Zeolites can provide adsorption sites with exchangeable cations for ammonium ion and porosity for free ammonia [13], with ion exchange and molecular adsorption being the main mechanisms, respectively. Although the latter is in significant importance especially in practice due to various pH feeds needed to deal with, few reports could be found on the contribution of molecular adsorption to the whole process.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolites can provide adsorption sites with exchangeable cations for ammonium ion and porosity for free ammonia [13], with ion exchange and molecular adsorption being the main mechanisms, respectively. Although the latter is in significant importance especially in practice due to various pH feeds needed to deal with, few reports could be found on the contribution of molecular adsorption to the whole process.…”
Section: Introductionmentioning
confidence: 99%
“…As one cation invades a zeolite structure, it can be adsorbed on the external surface of the channels or exchanged with the original cation that occupies the zeolitic cages. According to the fundamentals of ion exchange between solid and liquid phases [7,8], ion exchange between a zeolite frame and the aqueous ammonium solution can be expressed by the following Equation 1:…”
Section: Percentage Of Ion Exchange and Adsorption In Different Concementioning
confidence: 99%
“…Natural zeolites, including clinoptilolite [1], mordenite [4], erionite [5], and chabazite [6] have been widely utilized in water purification. Previous studies revealed the mechanisms of NH 4 + removal through ion exchange and adsorption in different zeolites [7,8]. Mordenite and clinoptilolite have frequently been employed to remove ammonium [9].…”
Section: Introductionmentioning
confidence: 99%
“…(2015) [1][2][3][4][5][6][7][8][9][10][11][12] www.deswater.com doi: 10.1080/19443994.2014.1003334 adsorption onto zeolite are usually conducted at low ammonium levels (<200 mg L −1 ), due to the limited potential of ammonium adsorption (9-16 mg g −1 ) of natural zeolite [8,9]. Hence, it is always need to be treated by chemical or physical methods frequently before using for ammonium removal from landfill leachate, livestock wastewater, and effluents from anaerobic digestion tanks of livestock manure, which contain ammonium greater than 1,000 mg L −1 [10].…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…Being microporous aluminosilicate minerals with an average diameter of 0.6-1.5 nm (larger than that of NH þ 4 , 0.29 nm), zeolites can provide adsorption sites with exchangeable ions for NH þ 4 and porosity for free ammonia (NH 3 ) with ion-exchange and molecular adsorption being the main mechanisms [5]. Substitution of silicon by aluminum atoms in the crystal framework leads to extra negative charge to be balanced by surrounding counterions (such as Na + , K + , Ca 2+ , and Mg 2+ ), and these counterions are easily exchanged by other surrounding cations (like NH þ 4 ) in a contact solution.…”
Section: Introductionmentioning
confidence: 99%